First measurement of Ω0c production in pp collisions at √s=13TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Kroesen, Martin; López, Jorge; et al. (Physics letters, 2023)
The inclusive production of the charm-strange baryon Ωc0 is measured for the first time via its hadronic decay into Ω−π+ at midrapidity (|y|<0.5) in proton-proton (pp) collisions at the centre-of-mass energy s=13 TeV with the ALICE detector at the LHC. The transverse momentum (pT) differential cross section multiplied by the branching ratio is presented in the interval 2<pT<12GeV/c. The pT dependence of the Ωc0-baryon production relative to the prompt D0-meson and to the prompt Ξc0-baryon production is compared to various models that take different hadronisation mechanisms into consideration. In the measured pT interval, the ratio of the pT-integrated cross sections of Ωc0 and prompt Λc+ baryons multiplied by the Ω−π+ branching ratio is found to be larger by a factor of about 20 with a significance of about 4σ when compared to e+e− collisions.